# SOLUTION: solve by factoring x cubed-9x=0 y squared-2y-24=0

Algebra ->  Algebra  -> Polynomials-and-rational-expressions -> SOLUTION: solve by factoring x cubed-9x=0 y squared-2y-24=0      Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Polynomials, rational expressions and equations Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on Polynomials-and-rational-expressions Question 106565: solve by factoring x cubed-9x=0 y squared-2y-24=0Found 2 solutions by edjones, ashlyn.xo:Answer by edjones(7569)   (Show Source): You can put this solution on YOUR website!x^3-9x=0 x(x^2-9)=0 x(x+3)(x-3)=0 x=0, x=-3, x=3 . y^2-2y-24=0 (y-6)(y+4)=0 y=6, y=-4 . Ed Answer by ashlyn.xo(7)   (Show Source): You can put this solution on YOUR website! this equation cannot be factored, because there is no square root of GAME: think of 2 numbers that is the product to the 3rd term (-24) and the sum of the 2nd term (-2). These two numbers would be: -6,4 This is because: And: now, substitute these two numbers as the middle term in the equation: Now, common factor by GROUPING -Common Factor the first two terms -Common factor of is y -Common Factor the last two terms -Common factor of is 4 Therefore, the equation is now after dividing by the common factors. Take the equation and common factor again, this time the common factor being (y-6) Therefore,